Butterflies (Lepidoptera: Papilionoidea) of the Restinga de Cabedelo National Forest, Paraíba State, Brazil - Medeiros, Adalberto; Gualberto, Emanoel Pereira; Rodrigues, Rafael Pereira; Kerpel, Solange Maria (EntomoBrasilis, 2021)
Restinga forests are plant formations that occur on plains of quaternary sandy deposits along the Brazilian coast. Despite historical reduction of the Restinga forests, little effort has been made to know the butterfly fauna of these areas. This paper is an important contribution to the butterfly’s knowledge, being the second inventory in the Restinga forest of northeastern Brazil. The survey was conducted in the Restinga de Cabedelo National Forest (FLONA de Cabedelo, following the Portuguese abbreviation) and aimed to provide preliminary information on the butterflies richness in this region. A total of 89 butterfly species and 1,503 individuals were recorded at FLONA de Cabedelo. Hesperiidae was the richest family (34 species), followed by Nymphalidae (33) Pieridae (eight), Lycaenidae (seven), Riodinidae (five), and Papilionidae (two). In general, the butterfly fauna of the FLONA de Cabedelo is dominated by species widely distributed and commonly found in open or forested areas in Brazil. Five species are new records in Paraíba state: Calydna sturnula (Geyer), Theope foliorum (Bates), Cogia hassan (Butler), Vehilius inca (Scudder), and Chiothion asychis (Stoll). We suggest carrying out monthly samplings which will certainly increase the list of species herein presented.